Surgery cancelling at a teaching hospital: implications for cost management (Revista Latino-Americana de Enfermagem, 2007)
This study discusses the problem of surgery cancellation on the economic-financial perspective. It was carried out in the Surgical Center Unit of a school hospital with the objective to identify and analyze the direct costs (human resources, medications and materials) and the opportunity costs that result from the cancellation of elective surgeries. Data were collected during three consecutive months through institutional documents and a form elaborated by the researchers. Only 58 (23.3%) of the 249 cancelled scheduled surgeries represented costs for the institution. The cancellations direct total cost was R$ 1.713.66 (average cost per patient R$ 29.54); distributed as follows: expenses with consumption materials R$ 333.05; sterilization process R$201.22; medications R$149.77 and human resources R$1,029.62. The human resources costs represented the greatest percentile in relation to the total cost (60.40%). It was observed that most of the cancellations could be partially avoided. Planning on management; redesigning work processes, training the staff and making early clinical evaluation can be strategies to minimize this occurrence.